Novel c-Met inhibitor suppresses the growth of c-Met-addicted gastric cancer cells. Issue 1 (December 2016) - Park, Chi; Cho, Sung; Ha, Jae Du; Jung, Heejung; Kim, Hyung; Lee, Chong; Jang, In-Young; Chae, Chong; Lee, Heung; Choi, Sang
Abstract Background c-Met signaling has been implicated in oncogenesis especially in cells withc -met gene amplification. Since 20 % of gastric cancer patients show high level of c-Met expression, c-Met has been identified as a good candidate for targeted therapy in gastric cancer. Herein, we report our newly synthesized c-Met inhibitor by showing its efficacy both in vitro and in vivo. Methods Compounds with both triazolopyrazine and pyridoxazine scaffolds were synthesized and tested using HTRF c-Met kinase assay. We performed cytotoxic assay, cellular phosphorylation assay, and cell cycle assay to investigate the cellular inhibitory mechanism of our compounds. We also conducted mouse xenograft assay to see efficacy in vivo. Results KRC-00509 and KRC-00715 were selected as excellent c-Met inhibitors through biochemical assay, and exhibited to be exclusively selective to c-Met by kinase panel assay. Cytotoxic assays using 18 gastric cancer cell lines showed our c-Met inhibitors suppressed specifically the growth of c-Met overexpressed cell lines, not that of c-Met low expressed cell lines, by inducing G1/S arrest. Inc -met amplified cell lines, c-Met inhibitors reduced the downstream signals including Akt and Erk as well as c-Met activity. In vivo Hs746T xenograft assay showed KRC-00715 reduced the tumor size significantly. Conclusions Our in vitro and in vivo data suggest KRC-00715 is a potent and highly selective c-Met inhibitor which may have therapeutic potential in gastric tumor with c-Met overexpression.